The Influence Of Church Music On The Enthusiasm Of The Gereja Beth-El Tabernakel Kristus Alfa Omega (GBT KAO) Juwana Congregation In Attending Worship - Simanjuntak, Michael; Sejati, Irfanda Rizki Harmono (Universitas Negeri Semarang, 2021)
Gereja Beth-El Tabernakel Kristus Alfa Omega (GBT KAO) Juwana is one of the churches in Juwana with a diverse congregation. With this diversity, GBT KAO Juwana tries to provide worship that is considered capable of the needs of all congregations through the music presented. The problem that is often encountered in churches today is the lack of enthusiasm of the congregation when worship is taking place. Therefore, the formulation that can be studied in this study is how the influence of church music on the enthusiasm of the GBT KAO Juwana congregation in attending worship. This study used quantitative research methods. The data collection technique in this study used a questionnaire. The collected questionnaires were processed using a simple linear regression analysis technique using SPSS. The results show that (1) the correlations table obtained Pearson Correlation of 0,707 > 0,312 and a significance value of 0,000 < 0,05, (2) the coefficients table obtained 6,168 > 1,697 and 0,000 < 0,05 significance values, (3) the ANOVAa table obtained f count of 38,048 > 4,098 and a significance value of 0,000 < 0,05, (4) the model summary table obtained R square value of 0,500 = 50,0%. The conclusions in this study indicate that church music has a 50% effect on the enthusiasm of the GBT KAO Juwana congregation in attending worship.